PENGARUH KECERDASAN EMOSIONAL DAN SPIRITUAL SISWA TERHADAP AKHLAK SISWA DI SMP ISLAM TERPADU BINA INSANI KAYUAGUNG - Dimas Assyakurrohim; Fajri Ismail; Muhammad Win Afgani (CV. ADIBA AISHA AMIRA, 2023)
Education is a process of change or self-development of students in all aspects of life so that a complete personality is formed both as social beings and individual beings, so that they can adapt and live well in the wider community. Achieving a perfect character is the real goal in education. With high emotional intelligence and spiritual intelligence a person will be able to control his intellectual potential in education so that it is realized in meaningful success. This research is a quantitative research. This type of research is correlation research. This research was carried out by collecting data to be able to find out and determine a relationship between the two variables being measured. Correlation is a term to measure the level of strength of the relationship between variables. The purpose of this study, to find out how students' emotional intelligence and spiritual intelligence with student morals at Bina Insani Kayuagung Integrated Islamic Middle School, and to find out whether there is a significant relationship between students' emotional intelligence and student morals at Bina Insani Kayuagung Integrated Islamic Middle School